The Conceptualization of Metaphors in Umpasa of Traditional Batak Wedding Ceremony: A Cognitive Semantic - Saragi, Devi Melisa (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2025)
This study tries to investigate the types of metaphors found in a Batak traditional form of oral poetics called umpasa from the cognitive linguistic perspective. By implementing Conceptual Metaphor Theory by Lakoff & Johnson (1980) and Image Schema Theory by Cruse & Croft (2004), the research aims at identifying and analyzing how metaphorical expressions in umpasa reflect Bataknese cultural values such as happiness, wealth, and honor. This descriptive qualitative research has implemented an observation method with note taking technique to collect the data taken from a classical text entitled Tradisi Umpasa Suku Batak Toba dalam Upacara Pernikahan by Sitanggang (1996). The finding reveals that of the ten metaphors analyzed, they are predominantly structured as 7 structurals, and 3 ontologicals which function to conceptualize abstract cultural concepts such as family growth, life lineage, life purpose, willingness to accept teaching, social character of a person, soul (spiritual), collective social dynamics, social advancement, son and daughter. While, based on the perspective of image schema, the metaphors can be categorized as iteration, container-full, path, enablement, container-containment, unity-merging, center and center-periphery. Ultimately, the results also have demonstrated how traditional oral expressions cognitively structure and perpetuate the cultural values which offer insight into the embodied worldview of the Batak Toba people.